The 1960 Tsunami in Hawaii: Long-Term Consequences of a Coastal Disaster. (June 2017) - Lynham, John; Noy, Ilan; Page, Jonathan
Summary: On May 23, 1960, a devastating tsunami struck the city of Hilo on the island of Hawaii. This tsunami provides a unique natural experiment as the tsunami was unexpected, and the other Hawaiian Islands, which were not hit by the tsunami, provide an ideal control group that enables us to precisely identify what happened to the economy of Hilo. We use a synthetic control methodology (Abadie, Diamond, & Hainmueller, 2010), and find that fifteen years after the event, unemployment was still 32% higher and population was still 9% lower than it would have been had the tsunami not occurred.